PENGEMBANGAN AGROINDUSTRI TERINTEGRASI DI KAWASAN AGROWISATA BERBASIS NANAS DI KABUPATEN PEMALANG - Kartika Trianita; Anas Miftah Fauzi; Ade Iskandar (Jurnal Teknologi Industri Pertanian, 2020)
The development of integrated agroindustry in superior commodity-based agritourism becomes one of the programs to help to increase the villager’s welfare. Complete and effective planning is needed to develop integrated agroindustry in agritourism with less risk of failure in implementation. The objective of this research was to develop an integrated agroindustry in pineapple-based agritourism in Pemalang Regency, including to determine the preferred agritourism facilities and pineapple-based products, and to determine the strategic location, and techno-economic analysis of pineapple-based factory. The respondent’s preferences for agritourism facilities and pineapple-based products were collected by using a questionnaire. The strategic location was determined by using the Exponential Comparison Method. The feasibility of a pineapple-based factory consisted of the calculation of NPV, IRR, Net B/C, PBP, and BEP. The results showed that the priority for procuring agro-tourism facilities was the activity of pineapple processing tours, gazebos, children's playgrounds, cafeterias or eating places, photo spots, souvenir shops, pineapple field tours, and internet access. The more preferred products were fresh pineapple, pineapple pie, jelly, sweets, jam, chips, juice, nata de pina, candy, syrup, and stick. Belik District was chosen as the strategic location for agritourism based on pineapple. The pineapple-based factory was feasible for an establishment with investment cost of Rp12,287,857,290; working capital of Rp5,292,243,387; NPV of Rp18,506,493,138; IRR of 19.03%; PBP of 4.26 year; Net B/C of 2.51; and BEPof 41.47%. Keywords: agritourism, agroindustry, honey pineapple, rural development